Effect of Metformin (MET) in Protection against Oxidative Stress and Pancreatic Damage Using an Animal Model - Rasool, Abeer Mansour Abdel; Mahmood, Isam Hamo (Pharmaceutical Science: New Insights and Developments Vol. 5, 2025)
Aim: The present study investigated the effects of metformin (MET) in protection against oxidative stress and pancreatic damage using an animal model, to assess the effect of metformin on oxidative stress in vivo and in vitro. Introduction: Diabetes mellitus is a worldwide health problem that has a deleterious impact on life expectancy and quality. People with diabetes have a higher oxidation state, which is detrimental to homeostasis. Numerous tissues have demonstrated the anti-oxidant qualities of metformin. An oral medication for diabetes called metformin aids in blood sugar regulation. Methods: This study investigated the effect of metformin on total antioxidant markers in the serum and pancreatic tissue of Alloxan-induced diabetic rats. Diabetic rats were randomised into five groups for treatment and received metformin (100,200,300 mg/kg) orally once daily for four weeks. The antioxidant potential of evaluated total antioxidant status (TAOS) in vivo and through DPPH (1,1-diphenyl-2-picryl-hydrazyl) scavenging assay at 517 nm in vitro. Results: A Considerable drop in elevated blood glucose level was observed in the alloxan-induced diabetic. At a dose of 100,200,300mg/kg demonstrated increase significantly improvement rate percentage in (M100, M200, M300) were (40.701 %),(48.063%) and (48.101%) respectively after end of treatment compared to diabetic group that decrease (-243.340%), TAOS were significantly increased in treated group than diabetic group" p= 0.000* ".The percentage of improvement rate elevation in treatment M100, M200, and M300 was (133.202 %,148.433% and 194.358%) respectively, compared with diabetic, while that percentage was decreased (-65.677%). Also, it improved pancreas histopathology compared to the diabetic control group it improved pancreas histopathology compared to the diabetic control group Antioxidant activity using DPPH was found to increase in a concentration-time-dependent manner IC50 of metformin (498.0 µg/ml), while ascorbic acid IC50 (µg/ml 29.62). Conclusions: In "alloxan-induced diabetic rats", metformin provides "protective actions" against free radicals and oxidative stress, as well as improving pancreas tissue histology and lowering blood glucose levels.